(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this study is to determine the effectiveness of recognition on the performance of rank-and-file employees in McDonald’s Sm Novaliches Branch in terms of recognition, rewards, promotion, and employee relations. Performances: quality of output, employee commitment, employee speed. The researchers are motivated to conduct this study entitled “Effectiveness of Recognition to the Performance of Rank-and-file Employees of McDonald’s Branch in SM Novaliches, Quezon City” to give an Action Plan to the problem of the effectiveness the employee performance of having not appreciated by the company in the case of doing their job well but not having a recognition. This study will benefit both the employees and the organization. Employees can seek opportunities for their careers as they can use their knowledge, skills, and expertise in the food industry. Rank-and-file not only want good salaries and benefits, but they want to be treated fairly as well, to make a strong contribution to the association through their hard work, and to be valued and appreciated for their hardship. The result of this study reveals the effectiveness of recognition on the performance of rank- and-file employees in terms of recognition, rewards, promotion, and employee relations. Performances, quality of output, employee commitment, and employee speed are effective. The problem encountered in terms of favoritism and kinship, and there is an action plan that can be proposed in the sustainability of effectiveness of recognition to the performance which is store rotation practices of management staffs or crew and develop an active anti- kinship & anti-favoritism policy then conduct a follow-up leadership training for the management. This study recommended that management continue to implement recognition and focus on their performance. Such as recognition, rewards, promotion, and employee relations. Performances: quality of output, employee commitment, employee speed. The rank-and-file performance will be a strong basis for management to recognize them.